CH3NH3PbI3−xBrx perovskite solar cells via spray assisted two-step deposition: Impact of bromide on stability and cell performance. (5th July 2017) - Chai, Gaoda; Luo, Shiqiang; Zhou, Hang; Daoud, Walid A.
Abstract: Fully converting the lead salt to perovskite is crucial for the performance of perovskite solar cells via the two-step deposition method. In this study, full conversion of PbI2 to perovskite is achieved via a spray assisted two-step deposition method with excess CH3 NH3 I sprayed onto the PbI2 layer. The influence of adding CH3 NH3 Br in the PbI2 solution in the first step on the resulting solar cells is investigated. The perovskite solar cells show significant increase in power conversion efficiency after one-night storage where a process of Br ion diffusion from Br-rich to I-rich regions is proposed. The study provides an alternative approach for incorporating Br and may help explaining the contradiction of reported conversion efficiency trends. Graphical abstract: Highlights: Fully converting PbI2 to perovskite is achieved via a spray assisted two-step deposition with excess MAI sprayed on PbI2 The influence of MABr addition in PbI2 solution on solar cell performance is discussed for the first time A Br ion diffusion process is proposed to explain the increase in efficiency after one-night storage